2014
DOI: 10.1111/1471-0528.12838
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhoids and anal fissures during pregnancy and after childbirth: a prospective cohort study

Abstract: Objective To identify the incidence and risk factors of haemorrhoids and fissures during pregnancy and after childbirth.Design Prospective observational cohort study.Setting University hospital and outpatient clinics in Lithuania.Population A total of 280 pregnant women followed up until 1 month after delivery.Methods Women were examined four times through pregnancy and after delivery; those that developed peri-anal diseases were compared with those that did not.Main outcome measures Incidence, time and risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
64
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 17 publications
(38 reference statements)
13
64
4
7
Order By: Relevance
“…were similar to this study in several respects. They too followed a cohort of women prospectively during pregnancy (Poskus during the first and third trimester, Abramowitz in the third trimester) and postpartum . Abramowitz et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were similar to this study in several respects. They too followed a cohort of women prospectively during pregnancy (Poskus during the first and third trimester, Abramowitz in the third trimester) and postpartum . Abramowitz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Poskus et al . reported a prevalence of peri‐anal problems of 43.9% from the first trimester until 1 month postpartum. In our study, a higher percentage of women with anal problems was found, with 68.5% of the women complaining of anal symptoms from the second trimester until 3 months postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some 40% of women will develop haemorrhoids during pregnancy, usually in the third trimester, or within the first month after delivery 50. Symptoms are believed to resolve shortly after birth, and intervention during pregnancy is therefore usually avoided.…”
Section: Managementmentioning
confidence: 99%
“…The most common consequences of long term constipation are hemorrhoids and anal fissures [5]. Several factors can be mentioned as potential reasons for the symptom: slower gastrointestinal (GI) transit time, higher plasma level of progesterone and mechanical obstruction [6].…”
Section: Introductionmentioning
confidence: 99%